Low Purine Diet Literacy in an Effort to Overcome Uric Acid Problems (HEALTH CARE: JURNAL KESEHATAN, 2025)
Consumption of foods high in purines will lead to an increase in uric acid levels in the blood. A low-purine diet is important to understand in efforts to manage or prevent high uric acid levels. This study aims to assess the literacy of a low-purine diet in addressing uric acid problems. Method: A quantitative descriptive research design with a cross-sectional approach. This research was conducted in the working area of the Umban Sari Health Center in the Sri Meranti Kelurahan, Pekanbaru, with 71 respondents selected based on inclusion criteria using accidental sampling technique. The analysis used was univariate and bivariate analysis with chi-square testing. This study used a low-purine diet literacyquestionnaire and a uric acid prevention questionnaire. Results: Diet literacy (knowledge) about purines was sufficient in 56 respondents (78.9%), while the efforts for uric acid prevention and control were categorized as good in 50 respondents (70.4%). The statistical test showed a p-value of (0.000) < α (0.05), which indicates that low-purine diet literacy isassociated with efforts in the prevention and control of uric acid. Conclusion: Low-purine diet literacy is related to the efforts for the prevention and control of uric acid.